INFLUENCE PRICE, SERVICE QUALITY AND TIME EFFICIENCY ON CUSTOMER INTEREST IN SUBSCRIBING TO ONLINE TRANSPORTATION ( GRAB ) AT THE FACULTY OF TEACHER TRAINING AND EDUCATION (FKIP) PRIMA INDONESIA UNIVERSITY - Tania, Silvia; -, Rickyks; Thomas, Calvin; Suryanita, Junianda; Ginting, Roy Dedi Ansarika; Bako, Evi Novalin (Jurnal Ipteks Terapan, 2024)
Grab is an application founded by Anthony Tan and Tan Hooi Ling in 2011 and began to be present in Indonesia in May 2014. Grab is very helpful in providing online transportation services to the public so it is in great demand by the public. Time Efficiency is the ability to use time so that not too much time is wasted, instead it is spent on the right things. In this research, the author is interested in researching the time efficiency variable because not many studies have used this variable. Simultaneously, price, service quality and time efficiency have an insignificant effect on customer interest in subscribing to online transportation services Grab at the Faculty of Teacher Training and Education, English Language Study Program , Prima Indonesia University. For Grab , the author hopes that this research can be used as information about what things influence customer interest in subscribing and also as a reference in improving facilities to increase customer interest. For future researchers, the author hopes that this research can be used as additional information for further research and adding variations to other variables which may also influence customer interest